Practical methods for optimal control using nonlinear programming - Betts, John T. 1943- (Society for Industrial and Applied Mathematics, 2020)
The third edition focuses on the direct transcription method for optimal control and includes new material on implicit Runge-Kutta discretization techniques, new chapters on partial differential equations and delay equations, and over seventy test problems and open source FORTRAN code for all of the problems.
Keywords: Nichtlineare Optimierung; Optimale Kontrolle; Control theory; Mathematical optimization; Nonlinear programming